The Influence of Big Book Media on Children's Empathetic Behavior - Rahayu, Maulina; Tahajudin, Didin (LPPM Universitas Primagraha, 2023)
This research discusses the influence of using big-book media on children's empathetic behavior. The research method used is quasi-experimental. This research aims to increase children's empathetic behavior by using big book media. Based on the results of the t-test, the post-test scores of the experimental and control groups show that the significance value is 0.005. The significance value states that it is smaller than 0.05. then it can be stated that the hypothesis is accepted, which means there is a significant difference between the post-test results of the experimental group and the control group. Thus, it can be concluded that there is a significant difference in the posttest results of the experimental group whose learning used big book media and the control group whose learning used oral stories.